Role of ketamine in treatment-resistant depression - Joanna Dmochowska; Marcin Ciechański; Joanna Cieszkowska; Julia Czerwik; Marta Czubala; Patrycja Felisiak; Wiktor Gąska; Karol Kanon; Edyta Witkowska (Journal of Education, Health and Sport)
Introduction: Depression, affecting 350 million people globally, is a leading cause of disability. Common symptoms include low mood, sadness, guilt, anxiety, and suicidalthoughts. Current treatments, mostly monoamine-based antidepressants, have limitations such as delayed effects and low efficacy, with over 60% of patients not achieving lasting remission. Ketamine, an NMDA antagonist, has shown rapid antidepressant effects, and research suggests glutamatergic dysfunction plays a role in TRD, highlighting the need for faster, more effective treatments.